MON-208 Association Study of AMH Promoter Polymorphisms and Serum AMH Levels in PCOS Patients - Moolhuijsen, Loes (J Endocr Soc, 2019)
Polycystic ovary syndrome (PCOS), the most common endocrine disorder in women, is diagnosed based on three criteria, including a polycystic ovarian morphology (PCOM). Although the etiology of PCOS is not fully understood, a genetic component has been demonstrated. Women with PCOS have elevated serum Anti-Müllerian Hormone (AMH) levels, a hormone known to reflect the ovarian reserve. Furthermore, the AMH production per follicle is suggested to be higher in PCOS patients and this combined implies an aberrant regulation of ovarian AMH expression. Currently, some transcription factors, such as FOXL2 and SF1, have been demonstrated to play a role in the ovarian regulation of AMH promoter activity. However, still little is known about AMH gene regulation, particularly in women with PCOS. Hence, the aim of this study was to investigate the association of single nucleotide polymorphisms (SNPs) in the AMH promoter on serum AMH levels in a cohort of PCOS patients. A candidate gene association study was conducted. All two-allelic SNPs located in or nearby the AMH promoter (Chr19:2,245,353 – 2,250,827bp) with a minor allele frequency > 1% and an imputation quality r(2) threshold above 0.75 were included. We included Caucasian PCOS women, diagnosed based on the Rotterdam criteria. AMH levels were measured with the picoAMH assay (Ansh Labs®, Houston, Texas, USA). The association between SNPs and serum AMH levels was assessed by linear regression with Wald test of significance, allele carrier model analysis with one-way analysis of covariance (ANCOVA). All statistical models were adjusted for age, BMI and total follicle count (TFC). AMH levels were natural log transformed to obtain a normal distribution. A p-value below 8.51e-03 was considered as statistically significant, based on Matrix Spectral Decomposition with an effective number of independent variables (VeffLi) of 6. All analyses were performed using R studio. We assessed 11 SNPs in 700 Caucasian PCOS women. Human AMH promoter polymorphism rs10406324 (-220 A/G) was associated with serum levels of AMH in the linear regression analysis (β = 0.52, p=6.08e-07). This association was also present in the dominant carrier model (AA: 9.85 ng/ml ± 0.27 (n=645) vs AG/GG: 7.60ng/ml ± 0.84 (n=54/n=1), p=6.48e-05, F = 16.2). The association of TFC and the polymorphism rs10406324, corrected for Age, BMI and AMH, showed an inverse trend compared to serum AMH levels (β=-8.00, p=3.75e-03), however this result was not significant in the carrier model (AA: 42.2 ± 0.88 (n=645) vs AG/GG: 43.6 ± 2.41 (n=54/n=1), p=0.60, F = 0.281). Moreover, this SNP was not in LD with any other SNP in the selected region. The human AMH promoter polymorphism rs10406324 is associated with serum AMH levels in Caucasian PCOS women. Replication and functional analyses are necessary to further elucidate the mechanisms by which this SNP affects the AMH promoter activity.